Factors affecting informal learning activities of the millennial generation - Leby, Jasmine Lau; Abd Rahim, Nur Aira; Syed Abdullah, Sharifah Intan Sharina; Che Me, Rosalam (Faculty of Education Department Primary Education, Ankara University, 2020)
The emergence of learner-centred pedagogy and the rise in learners’ demands for independence have amplified the importance of informal learning spaces apart from the conventional libraries. Universities, as the providers of physical infrastructure, need to consider a broad spectrum of learning activities and the environment in fulfilling the spatial demands of new generation learners. In line with that, this research seeks to investigate the effects of the physical (comfort, aesthetics, ICT facilities, layout) and social dimensions (privacy, interaction, autonomy) on students’ learning activities. Survey questionnaires were administered to 450 undergraduate and postgraduate students at a public university in Malaysia. This study used Smart-PLS to assess both the measurement and structural models. The results indicated that comfort, aesthetics, layout, interaction and autonomy were significant predictors of individual study activities in closed and quiet settings. Individual study activities in open and busy settings were determined by aesthetics and privacy. The interaction was the sole factor that affects collaborative study activities in closed and quiet spaces while the combination of interaction and autonomy significantly explained collaborative study activities in open and busy spaces. The findings revealed that students’ voices should be considered as their participation is an important enabler for the blueprint of effective informal learning spaces.